Narratives of pain: individual and contextual factors in somatic symptom disorder - Bernáldez Jaimes, Germán Benito; Oudhof van Barneveld, Johannes; Robles Estrada, Erika; Domínguez Espinosa, Alejandra Del Carmen (Acta Universitaria, 2019)
Somatic symptoms disorder (DSS) is defined as the presence of symptoms of a physiological nature without explanation and with constant concerns related to health that affect the person's life. The aim of the present qualitative study is to identify through a narrative analysis the individual from the city of Toluca Mexico and contextual factors that increase the presence of this psychopathology in six clinical patients with TSS, who accepted to participate in this study by an informed consent,, through in-depth interviews based on personality, automatic thoughts, coping strategies, vital events, and the perception of parenting. The conclusion of the study is that neuroticism and introversion, along with the perception of lack of support and family orientation, the presence of ideas of guilt, self-criticism, tendency to emotional restraint and positive reassessment as common factors in the participants with SSD tend to increase the perception of the discomfort and conflicts with their vital relationships.